(untitled) (UNIZIK Journal of Marketing, 2026)
This study investigates the relationship between financial leverage and firm performance among listed consumer goods companies in Nigeria, with a specific focus on whether the relationship is linear or follows an inverse U-shaped pattern. Using an ex post facto research design, panel data were collected from 16 firms over the period 2013–2024, yielding 192 firm-year observations. Financial leverage was measured by short-term, long-term, and total debt ratios, while performance was proxied by return on assets (ROA), with return on equity (ROE) and gross profit margin (GPM) used for robustness. Fixed effects regression and system generalized method of moments (GMM) were employed. The results show that all three leverage measures have significant negative linear effects on ROA. However, when a quadratic term is introduced, a strong inverse U-shaped relationship emerges, with an optimal total debt ratio of approximately 27%. This optimal level is well below the sample average of 44%, implying that most firms operate beyond their value-maximizing leverage. The findings support the trade-off theory of capital structure and remain robust across alternative performance measures, different leverage definitions, and exclusion of the crisis period. The study recommends that managers target leverage within the optimal range and that policymakers focus on reducing borrowing costs and foreign exchange risks.